The Positive Effects of Problem-Based Learning Activities Toward Indonesian EFL Learners' Productive Language Skills - Kristian Florensio Wijaya (Journal of English Teaching, 2022)
Abstract With the rapid globalization occurring all around the globe, educational landscapes also underwent some dramatic shifts in terms of teaching methods, policy-makers, and school culture. One of those indispensable trajectories that need to be taken into account by EFL educators is the pedagogical approach. Since learners no longer learn directly from one-on-one interaction with their teachers, it has been high time for educationalists to supersede their teaching-centered with the student-centered learning approach. In Indonesian EFL productive language learning contexts; speaking and writing, it is strongly believed that problem-based learning activities will enable learners to be more confident, autonomous, spirited, and proficient speakers as well as writers. This present qualitative study was plied in the support of document analysis by integrating 30 prior problem-based learning studies held in our archipelago in order to encourage Indonesian ELT experts, practitioners, and policy-makers to start to incorporate this student-centered learning approach in their both speaking and writing learning vicinities. The obtained results revealed 3 positive L2 productive language-learning merits potentially promoted by problem-based learning activities namely: 1) Learners can be more productive L2 academicians, (2) Learners transformed into more high quality and autonomous L2 writers, and (3) Learners progressively became more confident as well as proficient L2 speakers. Following all of these 3 core beneficial productive L2 learning values, contextual, hands-on, and pleasurable problem-based learning design should be well established at the commencement of speaking and writing learning activities to disseminate more holistic learning outcomes progressively for learners. Keywords: Problem-based learning, Indonesian EFL Learners, speaking, writing